2008
DOI: 10.1128/aac.01488-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lipid Amphotericin B Preparations in Treating Murine Zygomycosis

Abstract: We compared the efficacies of liposomal amphotericin B (LAmB) and an amphotericin B lipid complex (ABLC) in diabetic ketoacidotic (DKA) or neutropenic mice with disseminated zygomycosis. ABLC was as effective as LAmB in neutropenic but not DKA mice. Low-dose ABLC was less effective than LAmB at reducing brain fungal burdens in both models.Case reports and case series have documented successful outcomes after the treatment of zygomycosis with either liposomal amphotericin B (LAmB) or an amphotericin B lipid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 13 publications
2
41
0
4
Order By: Relevance
“…The authors' findings of improved survival with L-AMB treatment compared with that with ABLC treatment is not surprising, given the method of infection (intravenous injection) and the tissue sites that would favor the formulation with higher sustained bloodstream concentrations, i.e., L-AMB. When the findings of those studies are compared with our data, these studies underscore how differences in the efficacies of lipid AMB formulations cannot be extrapolated to all infection sites and immunosuppression backgrounds (11).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors' findings of improved survival with L-AMB treatment compared with that with ABLC treatment is not surprising, given the method of infection (intravenous injection) and the tissue sites that would favor the formulation with higher sustained bloodstream concentrations, i.e., L-AMB. When the findings of those studies are compared with our data, these studies underscore how differences in the efficacies of lipid AMB formulations cannot be extrapolated to all infection sites and immunosuppression backgrounds (11).…”
Section: Discussionmentioning
confidence: 89%
“…Ibrahim and colleagues utilized diabetic ketoacidotic (DKA) and neutropenic murine models to compare the activities of L-AMB and ABLC against disseminated mucormycosis (11). In the DKA model, treatment with ABLC at 7.5 or 15 mg/kg/day was associated with a significantly poorer rate of survival compared to that achieved with a similar L-AMB treatment dose.…”
Section: Discussionmentioning
confidence: 99%
“…60 The same investigators compared the efficacies of L-AmB and ABLC in diabetic ketoacidotic, as well as neutropenic mice, with disseminated mucormycosis, and found that ABLC was as effective as L-AmB in neutropenic but not ketoacidotic mice. In addition, low-dose ABLC was less effective than L-AmB at reducing brain fungal burdens in both models, 61 and the superior GDF penetration of L-AmB in the CNS compared to ABLC has been shown in a rabbit model of Candida meningoencephalitis. 62 Different findings were reported in another study in which the pharmacodynamics of ABLC and L-AmB were compared in a murine model of pulmonary mucormycosis.…”
mentioning
confidence: 99%
“…Studija je pokazala da kaspofungin izaziva znatno manje nefrotoksičnosti (2,6%) i drugih neželjenih reakcija (5%) nego LAmB (11,5% i 8%, respektivno). Pošto u Srbiji L-AmB nije dostupan, troškovi su uzeti za ABLC, jer je efikasnost ova dva oblika ista (10)(11)(12), a pretragom literature nije pronađena nijedna studija koja bi poredila kaspofungin i ABLC. U studiji koja je poredila bezbednost L-AmB i ABLC u empirijskoj terapiji febrilne neutropenije, LAmB je pokazao značajno manju učestalost groznice, drhtavice, kao i nefrotoksičnosti u odnosu na ABLC (13).…”
Section: Modelunclassified